In reply (15.05.2020) - Baum, Philip; Wiegering, Armin (Deutsches Ärzteblatt, 2020)
As Prof Mrozckowski correctly explains, DRG and OPS (Operationen- und Prozedurenschlüssel) codes are generally intended for billing for service rendered. They may bias the results of evaluations and are potentially inferior to data from clinical...
Gesehen am 16.02.2022
Letter to the editor: Mortality and complications following visceral surgery : a nationwide analysis based on the diagnostic categories used in German hospital invoicing data / by Dr. med. Philip Baum, Dr. med. Johannes Diers, Dr. med. Sven Lichthardt, Dr. med. Carolin Kastner, Prof. Dr. med. Nicolas Schlegel, Prof. Dr. med. Christoph-Thomas Germer, and PD Dr. med. Armin Wiegering in issue 44/2019